The Structural Effects of Metaphor-Elicited Cognitive and Affective Elaboration Levels on Attitude Toward the Ad - Kim, Jooyoung; Baek, Youngshim; Choi, Yang Ho (Journal of advertising, 2012)
This study examines the structural effects of cognitive and affective elaborations elicited by metaphoric advertising messages on the formation of A ad using the model developed by MacKenzie, Lutz, and Belch (1986). Results of an experiment with a 2 (low/high involvement) X 2 (hedonic/utilitarian) between-subjects design indicated that the level of metaphor-elicited cognitive elaboration had a significant effect on attitude toward advertiser, whereas the level of metaphor-elicited affective elaboration was significant on ad perceptions and ad credibility. In addition, affective elaborations had a greater overall impact, in terms of total effect, on A ad compared to the cognitive elaborations. Details about the effects of cognitive and affective elaborations under different product conditions are presented, and theoretical and managerial implications are discussed.